A Niccolite Structural Multiferroic Metal–Organic Framework Possessing Four Different Types of Bistability in Response to Dielectric and Magnetic Modulation - Zhao, Jiong‐Peng; Xu, Jian; Han, Song‐De; Wang, Qing‐Lun; Bu, Xian‐He (Advanced materials (Weinheim), 2017)
Multiple switchable physical properties have been demonstrated in one single niccolite structural metal–organic framework, [(CH3CH2)2NH2][FeIIIFeII(HCOO)6] (1), including (i) a reversible ferroelastic phase transition triggered by freezing the disordered (CH3CH2)2NH2+ cations, (ii) a thermally switchable dielectric constant transition accompanied by phase transition, and (iii) thermal and positive magnetic field driven magnetic poles reversal at low temperatures, attributed to different responses of the magnetization of FeII and FeIII sublattices to external stimuli. More interestingly, the exchange anisotropy between the two sublattices can also give rise to tunable positive and negative exchange bias fields. Straightforwardly, such diverse demonstrations of bistability in one single material (depending on the specific tuning way) will provide extra freedom and flexibility for the design of switcher devices. Four different types of bistability coexist in one single niccolite structural mixedvalence‐state metal–organic framework, including: i) a reversible ferroelastic phase transition triggered by freezing the disordered (CH3CH2)2NH2+ cations, ii) a thermally switchable dielectric‐constant transition, and iii) thermal and positive magnetic‐field‐driven magnetic poles reversal. Magnetic pinning with tunable exchange bias field is found.